Brief Intervention Among Mexican-Origin Young Adults in the Emergency Department at the USA–Mexico Border: Examining the Role of Patient's Preferred Language of Intervention in Predicting Drinking Outcomes†. (28th August 2018) - Oviedo Ramirez, Sandra; Alvarez, Miriam J; Field, Craig; Morera, Osvaldo F; Cherpitel, Cheryl; Woolard, Robert
Abstract : Aim of study was to determine if a patient's preferred language of intervention influences drinking outcomes among Mexican-origin young adults in the emergency department. Results indicate no significant differences in drinking outcomes among those who received BI in Spanish and BI in English. Abstract: Aims: Determine if the language in which brief intervention (BI) is delivered influences drinking outcomes among Mexican-origin young adults in the emergency department when controlling for ethnic matching. Short Summary: Aim of study was to determine if a patient's preferred language of intervention influences drinking outcomes among Mexican-origin young adults in the emergency department. Results indicate no significant differences in drinking outcomes among those who received BI in Spanish and BI in English. Methods: This is a secondary data analysis on data from 310 patients randomized to receive a BI completed in Spanish (BI-S) or English (BI-E), with 3- and 12-month follow-up. Outcome measures of interest were drinking days per week, drinks per drinking day, maximum drinks in a day and negative consequences of drinking. Results: There were no significant differences in drinking outcomes among those who received BI in Spanish and BI in English. Conclusions: Reduced drinking outcomes following BI among Mexican-origin young adults in the emergency department may not have been due to the language used to deliver intervention. Thus, our results provide evidence that language of intervention is not a crucial factor to achieve cultural congruence. In addition, our findings suggest that receiving the intervention is beneficial regardless of language, thus, facilitating real-world implementation.